2022
DOI: 10.3390/educsci12100728
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Problem-Based Learning (PBL) in STEM Education: Using Expert Wisdom and Research to Frame Educational Practice

Abstract: Developing teacher knowledge, skills, and confidence in Science, Technology, Engineering, and Mathematics (STEM) education is critical to supporting a culture of innovation and productivity across the population. Such capacity building is also necessary for the development of STEM literacies involving the ability to identify, apply, and integrate concepts from STEM domains toward understanding complex problems, and innovating to solve them. However, a lack of visible models of STEM integration has been highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 45 publications
2
41
0
4
Order By: Relevance
“…The nursing profession needs CT to make appropriate decisions in challenging situations. Therefore, new and student-centered educational methods, such as problemsolving-based learning strategies, can help improve nursing students' CT. Based on this study, students' tendency to CT increased in all dimensions after participating in problem-solving sessions, which was in line with the results of Seibert, Song, Liu and Pásztor (2021) (8,13,14).…”
Section: Discussionsupporting
confidence: 90%
“…The nursing profession needs CT to make appropriate decisions in challenging situations. Therefore, new and student-centered educational methods, such as problemsolving-based learning strategies, can help improve nursing students' CT. Based on this study, students' tendency to CT increased in all dimensions after participating in problem-solving sessions, which was in line with the results of Seibert, Song, Liu and Pásztor (2021) (8,13,14).…”
Section: Discussionsupporting
confidence: 90%
“…The ISS educational project contributed to reach the benchmarks of STEM readiness (Mattern et al, 2015), improving the STEM competences (Boon Ng, 2019) beyond the classic 4C skills (Triana et al, 2020). Both the Teams A and B practiced the PBL & PrBL (Smith et al, 2022) and the EDP (English & King, 2015) within a learning by doing pattern based on feeding the students' curiosity (Kowalski & Kowalski, 2015). Guided by two male supervisors, the brilliant performance of Team B (with four female members out of five) showed that the gender gap in STEM fields is not necessarily due to mismatching mentors, as conversely claimed by Kricorian et al (2020) and by Bilgin et al (2022a).…”
Section: Project's Achievementsmentioning
confidence: 83%
“…Developing teaching modules using the Problem-Based Learning (PBL) learning model is the right approach to improving students' problem-solving skills. PBL involves students actively in the process of solving and resolving real problems [57]. Several essential components in the developed teaching module help achieve learning objectives and facilitate students' problem-solving skills.…”
Section: Resultsmentioning
confidence: 99%